Symbiotic Bacterium-Derived Organic Acids Protect Delia antiqua Larvae from Entomopathogenic Fungal Infection - Fangyuan Zhou (American Society for Microbiology, 2020)
ABSTRACT Colonization resistance, i.e., the protective effects of associated microbiota for the animal host against pathogen infection, has been studied widely over the last 100 years. However, few molecules mediating colonization resistance have been identified. In the symbiosis formed by Delia antiqua and its associated microbes, six bacteria protect larvae from infection with the entomopathogen Beauveria bassiana, providing an ideal model to investigate the chemical mechanism for colonization resistance. Subsequently using this symbiotic system, we first compared effects of the six bacterial species, and one control bacterium (Klebsiella oxytoca) that showed no antifungal effects, on B. bassiana and its infection of D. antiqua. Second, metabolomic profiles of the six bacteria and K. oxytoca were compared to identify candidate metabolites that may prevent infection. Third, the concentrations of candidate metabolites in situ from axenic and nonaxenic larvae were determined. Finally, effects of artificial metabolite cocktails on B. bassiana and its infection of D. antiqua larvae were determined. Results showed that compared to K. oxytoca, the six bacteria produced a metabolite cocktail showing inhibitory effects on conidial germination, mycelial growth of B. bassiana, and fungal infection. Our work revealed novel molecules that mediate colonization resistance, which could help in developing chemical mechanisms of colonization resistance. Moreover, this work may aid in discovery and expansion of new bioactive antibiotics, promoting development of prophylactic and therapeutic approaches for treating infectious diseases. IMPORTANCE The protection of associated microbiota for their animal hosts against pathogen infection has been studied widely over the last 100 years. However, how those microbes protect the animal host remains unclear. In former studies, body surface microbes of one insect, Delia antiqua, protected the insect larvae from infection with the entomopathogen Beauveria bassiana. By comparing the metabolites produced by microbes that protect the insect and microbes that cannot protect the insect, the question of how the microbes protect the insect is answered. It turns out that body surface bacteria produce a metabolite cocktail that inhibits colonization of B. bassiana and consequently protects the insect. This work reveals novel molecules with antifungal activity, which may aid in discovery and expansion of new prophylactic and therapeutic natural chemicals for treating infectious diseases.